Isolasi dan identifikasi senyawa alkaloid dari buah Pare (Momordica Charantia L) menggunakan metode asam basa - Nusaputri, Yusriana (Maliki Interdisciplinary Journal, 2024)
Bitter melon is a fruit that has a stem that can reach almost two metres in length, and propagates with the help of a twisted vine. Bitter melon has a bitter taste because it comes from the alkaloid compound momordisin which is included in cucurbitacine. Alkaloids are active components that work as powerful drugs and immune cell activators that have the ability to eradicate viruses, bacteria, fungi, and cancer cells. This study aims to determine how the results of isolation of bitter melon (Momordica charantia L) alkaloid compounds using the acid-base method and identification of alkaloid compounds using UV-Vis. The results of extraction using the sonication method produced a yellowish brown ethanol extract with an extract mass of 2.6999 g and a yield of 2.69%. Then the results of isolation using the acid-base method using diethyl ether solvent brownish filtrate colour. Then using chloroform solvent, the filtrate colour became faded brown with a mass of extract weighing 7.8280 g and the resulting yield of 7.82%. Phytochemical tests using dragendoff reagent with orange precipitate results and using mayer reagent with yellow precipitate results. Identification of alkaloid compounds using UV-Vis spectrophotometer has a maximum wavelength of 270 nm.